(untitled) (Journal of the College of Basic Education, 2022)
The biopolymer used in this work was prepared from commercial sodium alginate, where the sodium alginate reacts with concentrated hydrochloric acid in a mixture of ethanol and water at a ratio of (30:70) and produces alginic acid, which is the prepared biopolymer as an adsorbent to remove ions of heavy elements (lead, cadmium and chromium) from solutions hydro. The factors that affect the adsorption process of these elements by this acid have been studied, represented by the treatment time. The pH of the adsorbent and the adsorbent concentration.The results showed that the used polymer was able to withdraw the ions of the three elements without exception, but with a significant relative difference.